Rediscovering a species not seen for a hundred years, Stathmopoda tacita (Meyrick, 1913) (Lepidoptera, Stathmopodidae), with its unusual fern-spore-feeding life history - Zong-Yu Shen; Yu-Feng Hsu (Biodiversity Data Journal, 2023)
Despite being the second largest group of vascular plants, ferns are scarcely reported being fed by insects when compared to angiosperms. Within these fern-feeding insects, lepidopterans are poorly represented and are restricted only to specific groups in this speciose order. The consumers specialising on fern spores are even scarcer in the order, with the majority being consumers of vegetative structures. Amongst the fern-spore-feeding Lepidoptera, Stathmopodidae is the family with the highest species diversity, even with a subfamily, Cyprininae Sinev, 2015, specialising on fern spores. However, fern-spore-feeding habit is not restricted to this subfamily. To understand the evolution of fern-spore-feeding within this family and to increase our knowledge of insect-fern evolution, detailed studies on fern-spore feeding stathmopodids are essential.The present study rediscovered a rare, fern-spore-feeding, stathmopodid micro-moth, Stathmopoda tacita (Meyrick, 1913), which has not been formally recorded or identified for more than 100 years. We documented the life history of this species and identified several species of Pyrrosia (Polypodiaceae, Platycerioideae) as host for the moth’s larvae. A re-description of the fern-feeding moth is also provided as the original description is obscure in terms of character diagnosis.